Identification of bacterial zoonotic respiratory pathogens in guinea pigs (cavia porcellus) raised as livestock In Paute, Ecuador - Zambrano Mila, Marlon Steven (2019)
Bacteria such as Streptococcus pneumoniae, Haemophilus influenzae, Mycobacterium tuberculosis and Staphylococcus aureus are among the most common human respiratory pathogens causing tuberculosis, pneumonia, sepsis, and meningitis. Cavia porcellus, known as guinea pig, is an animal used as research model for infectious diseases caused by viruses and bacteria. However, there are only few reports addressing its potential as a zoonotic vector in areas where it is raised as livestock, such as in Ecuador, where its population is estimated to be greater than 20 million. In this study, nasopharyngeal carriage of Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus and the infection with Mycobacterium tuberculosis, were evaluated in 80 guinea pigs from six farms in the Azuay province in Ecuador. For all the pathogens tested, 24 animals (30%) carried Staphylococcus aureus and 7 animals (9%) carried Streptococcus spp. No M. tuberculosis infection was detected and no H. influenzae was isolated. The S. aureus isolates were tested for methicillin resistance and virulence factors. We found six positive MRSA (Methicillin-Resistance-S. aureus) and three isolates were positive for Panton-Valentine Leukocidin (luk-PV) gene. Our results suggest the potential of guinea pigs as zoonotic vector for MRSA and Streptococcus spp. and claim for the implementation of public health policies for a safe production, management and consumption.